The Influence of AVO's Sustainability Campaign (Recycle, Reuse, Reduce) on AVO Skincare's Brand Image and Customer Loyalty - Urni Dhea Arda Riyanti; Fhena Annisa (Universitas Lambung Mangkurat, 2026)
The rapid growth of the skincare industry has raised environmental concerns, particularly related to packaging waste. In response to this issue, PT Avo Innovation Technology, an Indonesian cosmetics company, launched the #Avosustainableliving campaign (Recycle, Reuse, Reduce) as part of its sustainability initiative. This study aims to analyze the impact of the campaign on customer loyalty and brand image. Using a descriptive quantitative approach, data were collected through questionnaires distributed to 398 purposively selected AVO skincare users who follow the brand’s Instagram account (@Avolife). The results of simple linear regression analysis show that the campaign has a significant positive effect on customer loyalty (p < 0.001, R² = 0.882) and brand image (p < 0.001, R² = 0.830). In line with the Triple Bottom Line framework, these findings indicate that sustainability-oriented social campaigns can serve as effective strategic tools to strengthen consumer trust, enhance loyalty, and improve brand image within the competitive cosmetics industry.